MADRID CASADO, C.M.: «Filosofía de la Inteligencia Artificial». Pentalfa Ediciones, Oviedo 2024, 216 pp. ISBN: 9788478486502 - Castillo Moro, Manuel (IUS ET SCIENTIA, 2024)
Recensión de la obra: Filosofía de la Inteligencia Artificial